(untitled) (EAAE Annual Conference Proceedings, 2025)
Within the no-demolish approach, the proposal introduces a new design strategy based on a process of urban erosion for the areas in need of urban transformation. Observing in particular the vast areas born through the building boom of the 1960s, where the city has grown out of proportion, saturating green and common spaces, the proposed strategy becomes an alternative to total demolition, envisaging a process of progressive erosion which follows the characteristics of Benjaminian porosity. The term porosity, the pivotal theme of the text Naples by Walter Benjamin and Asia Lacjs (1925) has had a profound effect on architectural culture. Porosity has become a metaphor aimed at understanding urban space, characterized by complexity, stratifications, variations in volumes and voids, and processes of continuous transformation. Along this terms it could be possible to intervene within the urban fabric in concrete construction. The structural independence between the grid of pillars and beams and the horizontal surfaces of the floors, as well as between the façade walls and the internal partitions, makes it possible to insert voids on the ground floor as well as on the upper floors, with limited constructive and economic difficulties.